The Right to Freedom of Expression on Social Media in the Perspective of Human Rights and Islam - Ahmad, Pendi; Anggraeni, RR Dewi (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
Freedom of expression is one of the human rights (HAM) that is still often violated. Until now, there are still many people who do not respect and respect one's right to freedom of expression. The purpose of this study is to protect the right to freedom of expression on social media under Law on Information and Electronic Transactions (ITE) and the right to freedom of expression on social media from the perspective of human rights (HAM) and Islam. The method used in this research is normative legal research or instructional research. The results of the research obtained are that the protection of freedom of expression has not received adequate protection in Law No. 19 of 2016 amending Law No. 11 of 2008 on Information and Electronic Transactions (ITE). In this ITE Act there is only one article provision related to the right to freedom of expression through internet media, in this case social media, namely Article 27(3). The right to freedom of expression in social media belongs to the first generation of rights from a human rights perspective, which are identical to a person's civil, political and religious rights, save for a personality right that requires their fulfilment and protection.Keywords: Right to Freedom, Opinion, Islam AbstrakKebebasan berpendapat merupakan salah satu Hak Asasi Manusia (HAM) yang masih sering di langgar. Sampai saat ini, masih banyak orang yang belum menghargai dan menghormati hak kebebasan berpendapat seseorang. Tujuan dilakukan penelitian ini yaitu untuk mengetahui perlindungan atas hak kebebasan berpendapat di media sosial yang diatur dalam Undang-Undang tentang Informasi dan Transaksi Elektronik (ITE) dan untuk mengetahui hak kebebasan berpendapat di media sosial dalam perspektif Hak Asasi Manusia (HAM) dan Islam. Metode yang digunakan dalam penelitian ini adalah penelitian yuridis normatif atau penelitian doktrinal (doctrinal research). Hasil penelitian yang didapatkan yaitu perlindungan kebebasan berpendapat dalam Undang-Undang Nomor 19 Tahun 2016 Tentang Perubahan Atas Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik (ITE) belum mendapat perlindungan sebagaimana mestinya. Dalam Undang-Undang ITE ini, hanya terdapat satu ketentuan pasal yang berkaitan dengan hak kebebasan menyatakan pendapat melalui media internet dalam hal ini media sosial, yaitu dalam Pasal 27 ayat (3). Hak kebebasan berpendapat di media sosial dalam perspektif Hak Asasi Manusia, merupakan bagian dari hak generasi pertama yang identik dengan hak sipil, politik, beragama seseorang selain sebagai hak pribadi yang menuntut pemenuhan serta perlindungannya.Kata Kunci: Hak Kebebasan, Berpendapat, Islam